Perception of Clients’ Presenting Concern as a Function of Counsellor-Trainees’ Endorsement of Feminism - Lee, Dong Yul; Gee, Angel; Uhlemann, Max R. (Canadian Journal of Counselling and Psychotherapy, 2007)
The present study is an attempt to answer the question: Do novice clinicians' attitudes toward feminism influence their perception of the clients' problem? Our prediction was that for female clients, the degree to which counsellor-trainees endorse feminist attitudes is related to the attribution of causes, prognosis, and perceived counsellor understanding. After completing a scale assessing their endorsement of feminist attitudes, 150 counsellor-trainees viewed one of two videotaped counselling interviews in which a male counsellor interviewed a male or a female client about his or her presenting concern of depression. The counsellor-trainees were then asked to indicate their perceptions of the client's problem. The results showed no significant effect of counsellor-trainees' feminist attitudes on their perception of clients' presenting problem of depression.